An assessment of the relationship between Malaysia’s foreign direct investment and real wages in manufacturing sector / Azlina Hanif, Zuriyati Ahmad and Ruhaini Muda - Hanif, Azlina; Ahmad, Zuriyati; Muda, Ruhaini (2005)
The primary objective of this study is to examine the influence of real wages in Malaysia’s manufacturing sector on the inflows of foreign direct investment in Malaysia, in terms of direction and the extent to which the former affects the latter. Secondly, the research intends to identify the effect of FDI inflows on the real wages, in terms of the magnitude and direction of change. We hope to empirically confirm the conventional perception that FDI can subsequently raise the real wages of labor in a host country, given the little consensus as to whether FDI inflows bring improvements, skills upgrading, and wages in the host country’s manufacturing sector. The simultaneous equation model is used to investigate the two-way causal relationship between FDI and Real Wages, as an alternative method to Granger Causality Test. The technique of Two Stage Least Square is then employed in the regression. The findings suggest that real wage exerts a positive and significant effect on FDI and the reverse causation also holds true in similar trend.